Effects of COVID-19 and diabetes mellitus on AMPKα1 and IRS-1 amount in the blood plasma of patients - Tronko, M.D.; Pushkarev, V.V.; Sokolova, L.K.; Cherviakova, S.A.; Belchina, Y.B.; Kovzun, O.I.; Guda, B.B.; Pushkarev, V.M. (Доповіді НАН України, 2022)
The aim of the study was to determine the levels of AMPKα1 and IRS-1 in the blood of patients with diabetes mellitus and COVID-19. AMPKα1 and IRS-1 were determined using enzyme-linked immunosorbent assay (ELISA) (Elabscience, USA). AMPK controls the energy balance of the cell, stimulates catabolic processes – absorption of glucose, fatty acids, and their conversion by mitochondrial oxidation and glycolysis. With type 2 diabetes and obesity, its activity decreases, and the activity of protein kinases mTORC1/p70S6K increases, leading to phosphorylation of insulin receptor substrate-1 (IRS) and insulin resistance. The level of AMPKα1 in the blood of diabetic patients was significantly higher than in the blood of healthy people. The amount of AMPKα1 in the blood of people recovered from COVID-19 demonstrated the further growth of AMPKα1. The level of AMPKα1 was much higher in the blood of patients with DM during a COVID-19 disease. IRS-1 amounts in the blood plasma of patients with diabetes was higher than normal values. The level of IRS-1 in the blood plasma of patients with COVID-19 was much higher than in the blood of healthy people and patients with diabetes. The level of IRS-1 in the blood plasma may be one of the promising markers of COVID-19.